China and European Union Countries: Do Chinese partnerships boost cooperation results? - Costa, C. M.; Yichao, L. (JANUS.NET, e-journal of International Relations, 2023)
The People’s Republic of China and countries of the European Union (EU) have signed multiple diplomatic documents for cooperation under different types of conception. France was the first EU country to start a comprehensive partnership with China in 1997, and, by 2021, among the 27 EU member countries, 19 had already established partnerships with China (the exceptions were Estonia, Latvia, Lithuania, Luxembourg, Malta, Slovakia, Slovenia, and Sweden). Since the Belt and Road Initiative (BRI) was announced in 2013, 18 EU member states (except Belgium, Denmark, Finland, France, Germany, Ireland, Netherlands, Spain, and Sweden) have signed MoUs with China. What this study investigates, however, is why some of the countries have opted to sign a BRI MoU but not establish partnerships with China. On the other hand, some countries that have long had partnerships with China have deepened or strengthened those partnerships, yet have not signed a BRI MoU. The current study is therefore motivated to pose this main research question: To what extent does the Chinese partnership framework facilitate practical cooperation between EU countries and China? The study also poses these secondary questions: What are the main differences between these cooperation documents? Do such differences in documentation result in discrepancies in the nature of cooperation? From a bilateral state-to-state perspective, the study compares joint statements pertaining to Chinese partnerships with different EU countries, analyzing how closely they are tailored to each European country’s specificity. Through reviewing the literature, the authors gather data concerning the outcomes of cooperations on trade and investment between China and EU member states, and analyze any official diplomatic documents available.